Effects the Epley Maneuver on the Symptoms and Quality of Life Levels in Posterior Canal Benign Paroxysmal Positional Vertigo: Two Antalya District Hospitals Experience - Kar, Murat; Altıntaş, Mustafa (ENT Updates, 2020)
Objective: In this study, we aimed to investigate the ef fectiveness of the Epley maneuver performed without any additional medical treatment on symptoms and quality of life in patients diagnosed with canalithiasis type posterior canal BPPV with the Dix- Hallpike (DH) test in two District Hospitals of Antalya -Turkey. Methods: A total of 55 patients who were admitted to the ENT Departments Kumluca and Serik State Hospitals, Antalya between November 2019 and June 2020 with complaining of positional vertigo who were diagnosed as posterior canal BPPV with the Dix Hallpike (DH) test was included in this study. Results: Fifty-five cases with dizziness and vertigo complaints enrolled in our study. Thirty-four of the patients were male (%43.6), and 21 cases were female (%56.4). The ages of the patients were between 32 and 81with an average of 52.4±13.3 years. Statistically significant improvement was obtained at Vertigo Symptom Scale, Vertigo Dizziness Imbalance Symptom Scale, and Vertigo, Dizziness Imbalance health-related quality of life scale after the application of Epley maneuver Conclusion: In our study, Epley maneuver efficacy without any additional medical treatment was found to be very high in BPPV patients. As a result of this study, we wanted to emphasize that medical treatment to every patient presenting with dizziness and vertigo complaints is not a correct approach.